Calcium‐dependent protein kinase 5 links calcium signaling with N‐hydroxy‐l‐pipecolic acid‐ and SARD1‐dependent immune memory in systemic acquired resistance. Issue 1 (27th September 2019) - Guerra, Tiziana; Schilling, Silke; Hake, Katharina; Gorzolka, Karin; Sylvester, Fabian‐Philipp; Conrads, Benjamin; Westermann, Bernhard; Romeis, Tina
Summary: Systemic acquired resistance (SAR) prepares infected plants for faster and stronger defense activation upon subsequent attacks. SAR requires an information relay from primary infection to distal tissue and the initiation and maintenance of a self‐maintaining phytohormone salicylic acid (SA)‐defense loop. In spatial and temporal resolution, we show that calcium‐dependent protein kinase CPK5 contributes to immunity and SAR. In local basal resistance, CPK5 functions upstream of SA synthesis, perception, and signaling. In systemic tissue, CPK5 signaling leads to accumulation of SAR‐inducing metabolite N ‐hydroxy‐L ‐pipecolic acid (NHP) and SAR marker genes, including Systemic Acquired Resistance Deficient 1 ( SARD1) Plants of increased CPK5, but not CPK6, signaling display an 'enhanced SAR' phenotype towards a secondary bacterial infection. In the sard1‐1 background, CPK5‐mediated basal resistance is still mounted, but NHP concentration is reduced and enhanced SAR is lost. The biochemical analysis estimated CPK5 half maximal kinase activity for calcium, K50 [Ca 2+ ], to be c . 100 nM, close to the cytoplasmic resting level. This low threshold uniquely qualifies CPK5 to decode subtle changes in calcium, a prerequisite to signal relay and onset and maintenance of priming at later time points in distal tissue. Our data explain why CPK5 functions as a hub in basal and systemic plant immunity.